BSMA: scalable LoRa networks using full duplex gateways - Subbaraman, Raghav; Guntupalli, Yeswanth; Jain, Shruti; Kumar, Rohit; Chintalapudi, Krishna; Bharadia, Dinesh (MobiCom '22: Proceedings of the 28th Annual International Conference on Mobile Computing And Networking, 2022)
With its ability to communicate long distances, LoRa promises cityscale IoT deployments for smart city applications. This long-range, however, also increases contention as many thousands of devices are connected. Recently, CSMA has been proposed as a viable MAC for resolving contention in LoRa networks. In this paper, supported by measurements, we demonstrate that CSMA is ineffective in urban deployments. While gateways stationed at rooftops enjoy a long communication range, 70% of the devices placed at street level fail to sense each others’ transmissions and remain hidden, owing to obstructions by tall structures. We present Busy Signal Multiple Access (BSMA), where the LoRa gateway transmits a downlink busy signal while receiving an uplink transmission. The IoT devices defer uplink transmissions while a busy signal is present. Practically viable BSMA requires a full-duplex LoRa gateway – i.e., a gateway that can simultaneously receive and transmit in the same channel. We develop the first full Duplex LoRa gateway in the 915 MHz ISM band, overcoming challenges that arise from a 9× greater delay spread and the need for 1000× greater self-interference cancellation. Our implementation works with COTS LoRa devices and improves network capacity by 100% compared to CSMA in bursty loads while being fair to all IoT devices near and far.